2020
DOI: 10.3168/jds.2019-17762
|View full text |Cite|
|
Sign up to set email alerts
|

Use of indirect calorimetry to evaluate utilization of energy in lactating Jersey dairy cattle consuming diets with increasing inclusion of hydrolyzed feather meal

Abstract: A study using indirect calorimetry and 12 lactating multiparous Jersey cows (53 ± 23 d in milk at the beginning of the experiment; mean ± standard deviation) was conducted to evaluate the utilization of energy in cattle consuming diets containing increasing hydrolyzed feather meal (HFM). A triplicated 4 × 4 Latin square design with 35-d periods (28-d adaption and 4-d collections) was used to compare 4 different dietary treatments. Treatments contained (DM basis) HFM at 0% (0HFM), 3.3% (3.3HFM), 6.7% (6.7MFM), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…This experiment was designed to test the effects of RP Lys and RP His alone or in combination on milk production and composition, N and energy utilization, and AA status when feeding a base diet containing HFM. In our previous work, we observed a linear decrease in milk protein with increasing inclusion of HFM (Morris et al, 2020). Because HFM is low in Lys and His (NRC, 2001), the current experiment was designed to determine whether Lys, His, or both, are limiting in diets containing HFM.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…This experiment was designed to test the effects of RP Lys and RP His alone or in combination on milk production and composition, N and energy utilization, and AA status when feeding a base diet containing HFM. In our previous work, we observed a linear decrease in milk protein with increasing inclusion of HFM (Morris et al, 2020). Because HFM is low in Lys and His (NRC, 2001), the current experiment was designed to determine whether Lys, His, or both, are limiting in diets containing HFM.…”
Section: Resultsmentioning
confidence: 97%
“…This effect was consistent across treatments; thus, differences between treatment effects for energy partitioning may be interpreted with confidence. Although we strive to make animals comfortable and familiar with headboxes, a slight reduction in DMI was not unexpected (Morris et al, 2020). However, DMI was still within normal ranges, and we are unaware of alternative techniques that would allow us to make the measures described herein.…”
Section: Gas Consumption and Production Energy Utilization Nutrient Digestibility And Nitrogen Utilizationmentioning
confidence: 96%
See 1 more Smart Citation
“…In all 9 experiments, milk production and composition were quantified for 4 consecutive days. Cows were milked twice per day and fed once per day in all experiments except in Morris et al (2020b), where cows were milked 3 times per day, and Judy et al (2018), where cows were fed once or twice per day. In all studies, fecal and urine output was quantified by total collection for 4 consecutive days.…”
Section: Data Collectionmentioning
confidence: 99%
“…We recently observed that the NRC (2001) model underestimated dietary NE L content compared with measured NE L , when NE M was assumed to equal 0.080 Mcal per metabolic BW (BW 0.75 , MBW; Morris et al, 2020a). Furthermore, it has been shown that the efficiency of converting ME into NE L (denoted as k L ) is affected by diet (Moraes et al, 2015;Morris et al, 2020b). Historically, the NE L system assumed a constant or near constant k L (Moe et al, 1972;NRC, 2001).…”
Section: Introductionmentioning
confidence: 99%